The importance of gravel in concrete for construction (Jóvenes en la Ciencia, 2026)
Gravel, a fundamental construction material often underestimated due to its apparent simplicity, plays a crucial role in the strength, durability, and stability of structures. Its importance lies in its ability to provide a solid and reliable foundation in a variety of construction applications. Beyond its technical benefits, gravel stands out for its cost-effectiveness, thanks to its low price and easy availability, making it an attractive option for construction projects of all sizes. This paper will explore the different types of gravel, identify which is best suited for concrete, and discuss its importance and applications.